2014
DOI: 10.4239/wjd.v5.i4.471
|View full text |Cite
|
Sign up to set email alerts
|

Structured SMBG in early management of T2DM: Contributions from the St Carlos study

Abstract: Diabetes mellitus type 2 (T2DM) is a global pandemic that will affect 300 million people in the next decade. It has been shown that early and aggressive treatment of T2DM from the onset decreases complications, and the patient's active role is necessary to achieve better glycemic control. In order to achieve glycemic control targets, an active attitude in patients is needed, and self-monitoring of blood glucose (SMBG) plays a significant role. Nowadays, SMBG has become an important component of modern therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thus, under our study conditions, achievement of HbA1c target values together with type of hyperglycemia treatment was apparently the main drivers for SMBG-strips usage. Regarding these results, other authors have reported that SMBG aids physicians and patients to achieve target glycemic control levels that prevent the development of acute and chronic complications [21,22]. These results could be partly ascribed to the fact that high frequency of SMBG has been associated with earlier and more frequent changes in the clinician's prescription of diabetes medication [23][24][25].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, under our study conditions, achievement of HbA1c target values together with type of hyperglycemia treatment was apparently the main drivers for SMBG-strips usage. Regarding these results, other authors have reported that SMBG aids physicians and patients to achieve target glycemic control levels that prevent the development of acute and chronic complications [21,22]. These results could be partly ascribed to the fact that high frequency of SMBG has been associated with earlier and more frequent changes in the clinician's prescription of diabetes medication [23][24][25].…”
Section: Discussionmentioning
confidence: 96%
“…Nowadays, for most patients with type 1 (T1DM) and type 2 diabetes mellitus (T2DM) globally, self-monitored blood glucose (SMBG) has become an essential component of modern diabetic therapy to achieve the target level of glycemic control and to prevent hypoglycemia [ 12 ]. However, SMBG just gives snapshots of blood glucose concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence that the self-monitoring of BG (SMBG) and a healthy lifestyle are beneficial for controlling the disease, the implementation of effective SMBG and long-term lifestyle changes is a huge daily challenge [ 6 ]. The disadvantages of SMBG are related mainly to individual patients, who may lack the motivation for testing or may not be sufficiently aware of how/when to test and how to interpret the results [ 7 ].…”
Section: Introductionmentioning
confidence: 99%